DETERMINATION AND ESTIMATION OF PRESERVATIVES IN PACKAGED FOOD - kalva, sireesha; GANESH P, SAI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Packaged food and beverages are consumed all over the world for their nutritional value, durability, their quenching properties, stimulating effect, and for their medicinal value. Food additives are substances that are added to food or animal feed during processing or storage. They include antioxidants, preservatives, coloring and flavoring agents, and anti-infective agents. This study focuses on the determination of the content levels of sodium benzoate in different samples of commercially available food products in the local market. Methods: Food products selected are Sting Energy Drink, Listerine Cool Mint Mouthwash, Kissan Fresh Tomato Ketchup, and Dabur Hommade Imli Sauce. Identification tests for the presence of benzoic and its salts in food products were conducted. A standard graph for benzoic acid at different concentrations is drawn. The concentrations of benzoic acid in selected food products were determined and evaluated by rapid and simple ultraviolet spectrophotometric methods. Results: The results obtained from this study indicated that the quantity of benzoic acid in analyzed food samples was in the range of 18.3– 160.5 μg/mL. Conclusion: The optimum benzoic acid concentration to be in marketed food preservatives is 20–700 μg/mL. As the benzoic concentration in selected food products determined were in range, we found that all the selected samples are safe to use.